Holocene Fires and Ecological Novelty in the High Colombian Cordillera Oriental - Espinoza, Ismael G.; Franco-Gaviria, Felipe; Castañeda, Ivonne; Robinson, Charlotte; Room, Alex; Berrío, Juan Carlos; Armenteras, Dolors; Urrego, Dunia H. (Frontiers in Ecology and Evolution, 2022)
Rapid climate changes and the increasing presence of humans define the Holocene Epoch (11.6 calibrated kiloyears before present - hereafter kyr BP), when biological systems have faced the most recent and abrupt environmental changes. Understanding how biodiversity responds to extrinsic factors requires determining the effects of varying climatic conditions, changes in disturbance regimes, and increasing anthropogenic impacts. Despite being one centre for biodiversity, the potential synergies of long-term anthropogenic and climate changes in shaping areas of high Andean biodiversity have yet to be explored fully. Here we present new pollen and charcoal records from the Pantano de Monquentiva (hereafter Monquentiva) on the highlands of the eastern flank of the Colombian Cordillera Oriental (CCO) to document relationships between climate, vegetation, and fire through the Holocene. We found compositional transitions at 8.7, 6.1, and 4.1 kyr BP at Monquentiva resulting from the interaction of climate, fire, and human occupation. Reduced moisture and temperature caused a compositional shift in Páramo vegetation from ca. 8.7 kyr BP. Fire activity was recorded throughout the Holocene and increased slightly during the Mid-Holocene when regional and local fire decoupling suggested human activities as the source of ignition. Mid-Holocene fires had a large effect on the vegetation composition at Monquentiva which recorded a rapid shift at ca. 6.8 kyr BP. Fire activity increased sharply from 4.1 kyr BP, promoting the reorganisation of plant communities at 3.8 kyr BP. This shift in fire activity was likely related to more severe ENSO events and subsequently intensified by human activities after 3.8 kyr BP. Although high climatic sensitivity explains most Holocene vegetation changes in the eastern flank of the CCO, our study highlights the relevance of fire activity, uneven distribution of climatic variables, and human intervention to the composition of the vegetation we see today.